PERENCANAAN GEOMETRIK DAN TEBAL PERKERASAN KAKU PADA JALAN SIMPANG KOLAM-SIMPANG SEMAMBANG BARU - Isranur Annisa; Wulan, Wulanda Aprillia; Andi Herius; Akhmad Mirza (Politeknik Negeri Sriwijaya, 2024)
The government plans to build an alternative road at Simpang Kolam – Simpang Semambang Baru in Musi Rawas Regency, South Sumatra, to address the increasing traffic volume. This road is designed as a Class II A collector road with a planned speed of 80 km/h. The geometric design planning includes horizontal alignment, vertical alignment, and pavement using 25 cm thick rigid pavement, 12.5 cm lean concrete, and a 20 cm subbase layer. The construction will take 207 working days. Keywords : Road,Cost,Geometric,Design